2014
DOI: 10.1245/s10434-014-3526-8
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of Postoperative Morbidity and Mortality After Laparoscopic Radiofrequency Ablation of Liver Tumors

Abstract: This study describes the morbidity and mortality to be expected after a laparoscopic RFA procedure. Our results show that additional caution should be used to prevent bleeding complications in patients with tumors located in the right posterior sector and infections in patients with a history of BEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The safety of VLA for HCC had so far been reported for series of no more than 267 patients treated with RFA, and 203 treated with MWA . The vast majority of the complications described to date (in 2% to 45% of patients treated with VL RFA, and in 16% to 62% of those treated with VL MWA) were minor. The use of MWA has nonetheless been widely questioned because of the potentially higher risk of major biliary damage associated with the greater amount of energy delivered.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of VLA for HCC had so far been reported for series of no more than 267 patients treated with RFA, and 203 treated with MWA . The vast majority of the complications described to date (in 2% to 45% of patients treated with VL RFA, and in 16% to 62% of those treated with VL MWA) were minor. The use of MWA has nonetheless been widely questioned because of the potentially higher risk of major biliary damage associated with the greater amount of energy delivered.…”
Section: Discussionmentioning
confidence: 99%
“…Birsen et al [9] analyzed the 90-day morbidity and mortality of 910 patients who underwent a total of 1,207 laparoscopic RFA procedures for 2,890 malignant liver tumors between 1996 and 2012. In this large study, they found that laparoscopic RFA was associated with a complication rate of 4% (n = 50) and a mortality of 0.4% (n = 5).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the implementation of RFA under ultrasonic labeling in the treatment of patients with HCC disease, previous findings have confirmed that this method has many advantages such as no radiation on the human body, simple operation, and the ability to observe lesions in real time. However, in contrast to an ultrasonic image cannot be formed due to small liver lesions, no vessel violations and iso-echoic HCC, ordinary ultrasound labeling is inadequate as it is difficult to accurately locate the cancer tissue ( 16 18 ). Consequently, during the treatment of HCC by RFA, CEUS technology should be employed as it enhances image sharpness and contrast, detects enhanced blood flow data and the lesion infiltration range, which cannot be identified by ordinary ultrasound, thereby indicating the efficacy for more thorough treatment by RFA.…”
Section: Discussionmentioning
confidence: 99%